2015
DOI: 10.1016/j.invent.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Developing Internet interventions to target the individual impact of stigma in health conditions

Abstract: a b s t r a c t 8 A number of health problems are associated with significant stigma, a social phenomenon in which individuals 22 become the object of negative stereotypes. In addition to experiencing negative reactions from others, 23 stigmatised individuals and groups can experience harmful consequences when they internalise these negative 24 prevailing attitudes. The objective of this paper was to consider the potential to develop Internet-based health-25 related interventions explicitly targeting the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 103 publications
1
40
0
Order By: Relevance
“…Precisely, interacting with peers online can create greater social connectedness and feelings of group belonging that strengthen stigma resistance [54]. The Internet has the capacity to easily offer contacts with peers within one’s marginalized group as well as disclosure possibilities, both of those being key dimensions of stigma reduction strategies [55]. …”
Section: Resultsmentioning
confidence: 99%
“…Precisely, interacting with peers online can create greater social connectedness and feelings of group belonging that strengthen stigma resistance [54]. The Internet has the capacity to easily offer contacts with peers within one’s marginalized group as well as disclosure possibilities, both of those being key dimensions of stigma reduction strategies [55]. …”
Section: Resultsmentioning
confidence: 99%
“…Initial studies of Internet-based applications with people with persisting psychosis have indicated self-guided use of digital tools to be feasible with this population (1921). Moreover, the Internet is potentially empowering of people with mental illness in facilitating peer-to-peer connections (22) and is a means of presenting lived experience material in video format that may be useful in portraying positive hopeful views of peers with mental health problems (23). Hence, digital technology offers a number of possibilities for promoting learning from lived experience.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma has been defined by Thomas et al . as ‘an attribute or label (such as a particular diagnosis) that links individuals to negative social stereotypes.’ (p.352). Research has shown how negative language, such as apportioning blame, stereotyping (such as portrayals in the media) and judgemental remarks, have all been found to increase stigma .…”
Section: Resultsmentioning
confidence: 99%
“…A small body of literature has considered the potential for addressing stigma, mainly through attempts to increase the information available online regarding people's experiences of diabetes . These attempts included user‐generated content and sharing experiences through blogs or tweet chats; however, recently, messages about losing weight or healthy eating, obesity and diabetes have shifted the focus to the individual, identifying them as the person responsible for their health and ignoring the socio‐economic context within which they live .…”
Section: Resultsmentioning
confidence: 99%